Hubungan Antar Umat Beragama (Studi Tafsir Tematik Muhammadiyah) - Fahma Maulida; Nur Alifi; M. Fahrizat Adzkar (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2023)
Inter-religious relations have always been an interesting issue to study. On 1 November 2022 Religion Twenty (R20) was held in Bali involving religious leaders from around the world. This religious forum is a new step for all religious communities to establish good relations between religious communities so as to avoid divisions. This article aims to further explore the principles of inter-religious relations in the book of thematic interpretations by Muhammadiyah. This research is a type of library research. The results of this study indicate that there are three principles of inter-religious relations in the book of thematic interpretations by Muhammadiyah: 1) recognition of plurality and competition in goodness, 2) peaceful coexistence in inter-religious relations, and 3) justice and equality.